Role of methylprednisolone on mRNA expression of BAX, BCL-2 genein testicular torsion-detorsion of male albino Wistar rats - Muhammad Puteh Mauny; Raden Danarto; Didik Setyo Heriyanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Study Background : Testicular torsion is a genitourinary emergency most common in children and emergencies requiring second surgery in adolescents after acute appendicitis1. Testicular torsion is more common on the left with a 1.2: 1 ratio, which is probably caused by a slightly longer spermatic cord on the left2. Testicular torsion can occur at any age, but the peak incidence is at age 14, with a peak of second occurrence at 1 year of age3. At 1 year of age, testicular torsion is a major cause of acute scrotum (83%). At the age of 3 - 13 years, the most frequent diagnosis is the torsion of the testicular appendix. After the age of 17 years, epididymitis is the most frequent diagnosis (75%)4. Method: This study is an experimental study, post-test only control group design, the sample was randomly divided into 4 groups, 2 intervention groups and 2 control groups. In this study the independent variables are the duration of the right torsion-detection treatment of the testes and the injection of Methylprednisolone in Wistar male rats. The dependent variables are mRNA expression in apoptosis and anti-apoptosis genes in rats’ ipsilateral and contralateral testes. . Results and Discussion: In this study, two-way ANOVA is used to analyze data between groups. Significant decrease in BAX gene mRNA expression (p